Ethylcellulose oleogels with extra virgin olive oil: the role of oil minor components on microstructure and mechanical strength. (November 2018) - Giacintucci, V.; Di Mattia, C.D.; Sacchetti, G.; Flamminii, F.; Gravelle, A.J.; Baylis, B.; Dutcher, J.R.; Marangoni, A.G.; Pittia, P.
Abstract: The structuring of Extra Virgin Olive Oil with ethylcellulose and the role of oil minor compounds on oleogel structural and mechanical properties were investigated. To this aim a refining process, consisting of degumming, neutralization and bleaching steps, was applied to the oils to progressively remove specific minor components. At each step, the oils were characterized by free fatty acids and polyphenol contents, primary and secondary oxidation products and polarity of the solvent; the purified oils were then used to produce ethylcellulose-based oleogels. Large deformation tests such as Back Extrusion and Two Plates Compression Analysis were performed to investigate the mechanical properties of the oleogels, while the microstructure was studied by Atomic Force Microscopy. Results showed that the purification steps affected the chemical composition of the oils and their polarity which, in turn, influenced oleogel properties. From a microstructural perspective, a change in the size, diameter and shape of the pores in the gels produced with the purified oils was observed. Pore roundness and circularity decreased throughout the purification, with a progressive loss in roundness and circularity and a predominance of elongated and bean-shaped pores as minor compounds were selectively removed from the matrix. A decreasing trend in gel hardness was observed upon oil refining showing that minor compounds significantly affected also the mechanical properties of the oleogels. The polarity of the solvent and the presence of minor components were confirmed to be important parameters to determine the relation between ethylcellulose network characteristics and oleogel mechanical strength. From a multiple partial least regression MPLSR, it resulted that pores diameter, roundness and circularity were positively affected by polar and amphiphilic compounds like polyphenols while gel hardness was positively influenced by free fatty acids and total polar compounds. Graphical abstract: Image Highlights: Extra Virgin Olive Oil oleogels were structured with ethylcellulose. The role of oil minor compounds on oleogel physical properties was studied. Large deformation tests were performed to investigate the mechanical properties. Oleogels microstructure was studied by atomic force microscopy. Oleogel mechanical strength was affected by oil polarity and minor compounds.